2022
DOI: 10.1371/journal.pone.0268792
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the nail contamination with soil-transmitted helminths in schoolchildren in Jimma Town, Ethiopia

Abstract: Background Large-scale deworming programs have been successful in reducing the burden of disease due to soil-transmitted helminth (STH; Ascaris lumbricloides, Trichuris trichiura and hookworm) infections, but re-infection in absence of other measures is unavoidable. We assessed the role of nail contamination as a source of infection with the goal to evaluate the potential of nail clipping as a simple measure to further reduce STH-attributable morbidity. Methods A cross-sectional study was conducted in Jimma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
3
8
0
Order By: Relevance
“…Another study conducted in Argentina reported a prevalence rate of 28.4% among the 303 participants ( Rivero et al, 2018 ). In Ethiopia, a study by Tadege and colleagues found a % infection rate of 1% among the collected 600 samples ( Tadege et al, 2022 ). In Egypt, a study by Elmonir et al reported an infection rate of 8.6% among a total of 996 collected samples ( Elmonir et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study conducted in Argentina reported a prevalence rate of 28.4% among the 303 participants ( Rivero et al, 2018 ). In Ethiopia, a study by Tadege and colleagues found a % infection rate of 1% among the collected 600 samples ( Tadege et al, 2022 ). In Egypt, a study by Elmonir et al reported an infection rate of 8.6% among a total of 996 collected samples ( Elmonir et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This can result in fatigue, lack of concentration, reduced efficiency, and increased susceptibility to other diseases in children. Treating this infectious agent and the diseases it causes can impose significant costs on the healthcare sector ( Rivero et al, 2018 ; Tadege et al, 2022 ; Elmonir et al, 2021 ; Fan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies conducted in Jimma Town also reported prevalence of S. mansoni ranging from 5.0-28.7%. 20,21,28 Nationally, more than a third of children are estimated to be infected with S. mansoni , with high variability in different areas. 29 Even compared to the local situation, this study was conducted in primary schoolchildren with presumably higher risk of S. mansoni infection and re-infection rates due to the availability of freshwater bodies around the schools.…”
Section: Discussionmentioning
confidence: 99%
“…The study will be conducted in both Ethiopia and Uganda. The selection of these countries and the corresponding partners (Ethiopia: Jimma University; Uganda: Vector Control and Neglected Tropical Diseases Division, Ministry of Health of Uganda) were based on ongoing collaborations [20, 2936], the presence of an STH control program (Ethiopia: since 2015; Uganda: since 2003), and the availability of recent data on both the prevalence and intensity of STH infections [31, 32, 37]. Finally, both countries operate differently, allowing AI-DP evaluation in a fully equipped laboratory (Jimma University, Ethiopia) and a field setting (VCD, Uganda) that best mimic monitoring and evaluation (M&E) activities as part of the national STH deworming program.…”
Section: Study Population and Study Sitesmentioning
confidence: 99%
“…Uganda: since 2003), and the availability of recent data on both the prevalence and intensity of STH infecUons [31,32,37]. Finally, both countries operate differently, allowing AI-DP evaluaUon in a fully equipped laboratory (Jimma University, Ethiopia) and a field sekng (VCD, Uganda) that best mimic monitoring and evaluaUon (M&E) acUviUes as part of the naUonal STH deworming program.…”
Section: Inclusion Criteriamentioning
confidence: 99%